Health Sovereignty Under Conditional Generosity - A. Diallo; N. Mbele; L. Simpson; R. Johnson (Pan African Strategic Observatory, 2025)
We analyze the Kenya–United States Health Cooperation Framework as a contemporary case study of health-sector imperialism. We argue that the agreement reproduces a pattern already described in the Imperial Selection Model (ISM) and in the Diagnostic and Statistical Manual of Human Structural Pathologies (DSM-H): external powers select and reward local elites who accept asymmetrical control over strategic systems in exchange for conditional funding and symbolic prestige. Using documentary analysis of the 37-page framework, court filings by the Consumers Federation of Kenya (COFK), Kenyan constitutional provisions, and the emerging literature on data colonialism and pathogen sharing, we identify fifteen red-flag clauses. These concern long-term access to health data and genetic material, automatic acceptance of foreign regulatory decisions, one-way audit rights, digital infrastructure dependency, legal immunities for foreign actors, and escalating domestic financial obligations combined with easy aid withdrawal. We show how these clauses shift strategic control over surveillance, biological specimens and health decision-making toward the United States, while formally presenting the arrangement as a partnership for capacity building and pandemic preparedness. Our findings support three main claims. First, the framework is structurally incompatible with full health sovereignty under the Kenyan Constitution. Second, it fits the ISM prediction that imperial actors will attach control over data, specimens and decision rules to any renewed flow of funding. Third, at the level of collective psychology, the agreement normalises a chronic state of dependency in which the local population carries financial and epidemiological risk, while strategic and commercial benefits concentrate abroad. We conclude that African states require explicit health-sovereignty standards, independent review bodies, and binding benefit-sharing rules before entering similar frameworks. We propose a set of minimum safeguards and outline how the ISM and DSM-H can guide structured risk assessment for future health agreements in Kenya, the Democratic Republic of Congo (DRC) and beyond.
The Kenya–United States Health Cooperation Framework as a Case Study in Imperial Selection and Structural pathology